Building type basics for retail and mixed-use facilities (Wiley, 2004)
Provides the nuts-and-bolts material to begin designing a retail or mixed-use facility. Features project photographs, diagrams and floor plans, and sections and details. Provides need-to-know information on such essential topics as consensus-based decision making, site selection, renovation, code compliance, and more.